Analysis of students’ reading comprehension skills in indonesian language subject of fourth-grade students at SDN Barurambat Kota 1 pamekasan - Safitrih, Irene May Widiyani; Setyawan, Agung (Widyagogik, 2025)
This study aims to analyze the reading comprehension skills of fourth-grade students at SDN Barurambat Kota 1 Pamekasan in the Indonesian language subject. The research focuses on students’ mastery of reading comprehension indicators in accordance with the Merdeka Curriculum, including the ability to identify main ideas, understand explicit and implicit information, interpret vocabulary in context, draw logical conclusions, and evaluate the author’s purpose. This study employed a qualitative approach with a case study design. Data were collected through reading comprehension tests based on ten indicators, classroom observations, interviews with teachers and students, and documentation. The results revealed variations in students’ reading comprehension abilities. Students in the high-ability group demonstrated good literal and inferential comprehension, used active strategies such as summarizing, and showed strong motivation to read. Meanwhile, most students were in the moderate and low categories, showing difficulties in identifying implicit information, interpreting contextual vocabulary, and constructing coherent conclusions. These findings indicate that most students are still at the literal comprehension level, while inferential and evaluative skills remain underdeveloped. The study concludes that limited vocabulary mastery, low motivation, and the use of conventional teaching strategies hinder reading comprehension development. Therefore, teachers need to design contextual and student-centered learning strategies to improve comprehension skills holistically. The results of this research are expected to serve as a reference for strengthening school literacy culture and developing innovative reading instruction models.